Japanese Journal of Statistics and Data Science - Aoshima, Makoto; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
The aim of the Japanese Journal of Statistics and Data Science (JJSD) is to publish original articles concerning statistical theories and novel applications in diverse research fields related to statistics and data science. It also sometimes publishes review and expository articles on specific topics, which are expected to bring valuable information for researchers interested in the fields selected. The journal also contributes to broadening the coverage of statistics and data analysis in publishing articles based on innovative ideas. All articles are refereed by experts. JJSD is published by the Japanese Federation of Statistical Science Associations (JFSSA). The members of JFSSA are six Japanese statistics-related societies: the Japanese Society of Applied Statistics, the Japanese Society of Computational Statistics, the Biometric Society of Japan, the Behaviormetric Society, the Japan Statistical Society, and the Japanese Classification Society. These organizations jointly contribute to promoting the prestige of the journal and to ensuring that its readership and circulation are as wide as possible. This wide coverage provided by six statistics-related societies is a unique feature of the new journal both for contributors and for readers. The journal is also unique in combining traditional statistical science and relatively new data science. In order to make JJSD accessible to a wide range of readers, specific sections are planned for each issue of the journal, including sections on theory and methods, biometrics, computational statistics, econometrics, and other research fields. JJSD is the successor of the Journal of the Japan Statistical Society (JJSS) published by the Japan Statistical Society, and the Journal of the Japanese Society of Computational Statistics (JJSCS) published by the Japanese Society of Computational Statistics. In addition to these two societies, four societies of JFSSA will cooperate in publishing the journal.
Keywords: Statistics; Statistical Theory and Methods; Statistics and Computing/Statistics Programs; Statistics for Business, Management, Economics, Finance, Insurance; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Statistics for Life Sciences, Medicine, Health Sciences; Statistics for Social Sciences, Humanities, Law